The amphibians and reptiles of New York State : identification, natural history, and conservation - Gibbs, James P. (Oxford University Press, 2007)
This is the first guide yet produced to the amphibians and reptiles of New York State, a large and heavily populated state that hosts a surprisingly diverse and interesting community of amphibians and reptiles. This much needed guide to the identification, distribution, natural history and conservation of the amphibians and reptiles of New York State fill a long-empty niche. The book is the first comprehensive presentation of the distributional data gathered for the New York State Amphibian and Reptile Atlas project. With more than 60,000 records compiled from 1990-1999, this extraordinary and.